Exploring the dynamics of stroke survivors’ care dependency, fatigue, and coping strategy in their caregivers: a structural equation modeling analysis - Wang, Jinyao; Tu, Shuangyan; Cui, Jun; Yang, Rong; Jiang, Yan; Zhao, Lihong (Frontiers in Public Health, 2025)
AimsTo evaluate the interactions among stroke survivors’ care dependency, caregivers’ negative coping strategy, and fatigue.DesignDescriptive quantitative research design.SettingPatients with acute stroke and their caregivers were enrolled in a General Hospital in West China from July 2022 to April 2023.Primary and secondary outcome measuresData collection adopted the Care Dependency Scale (CDS), the Simple Coping Style Questionnaire (SCSQ), and the Fatigue Scale-14 (FS-14). Structural equation modeling was applied to test the hypothetical model. This study adhered to STROBE reporting guidelines.ResultsA total of 380 dyads with the mean age of stroke caregivers was 63.41 ± 12.87 years. The mean score for care dependency, fatigue, positive coping, and negative coping were 53.91 ± 15.95, 8.34 ± 3.58, 19.39 ± 7.05, and 8.06 ± 4.23, respectively. The structural equation model had a good fit index (χ2 = 12.595 (df 5), IFI = 0.993, GFI = 0.990, AGFI = 0.956, NFI = 0.988, TLI = 0.979, CFI = 0.993, RMSEA = 0.063, SRMR = 0.0213). It showed that the direct effect path coefficients of patients’ care dependency on caregivers’ fatigue (β = −0.22, 95% confidence interval (CI): −0.367, −0.097, p = 0.002) and negative coping (β = −0.31, 95% CI: −0.438, −0.155, p = 0.003) were statistically significant. The NIHSS score indirectly influenced caregivers’ fatigue (β = 0.023, 95% CI: 0.006, 0.051, p = 0.002) and negative coping (β = 0.204, 95% CI: 0.103, 0.303, p = 0.003) through the mediating effect of care dependency.ConclusionThis study indicated that stroke patients’ level of care dependency directly impacts their caregivers’ negative coping strategy and level of fatigue. The stroke’s severity might induce caregivers to engage in negative coping strategies and endure more fatigue when the patients’ care dependency played an indirect role. Researchers need to develop targeted interventions involving training caregivers to employ active coping strategies to confront the care burden.Implications for the profession and/or patient careBased on the treatment of stroke onset, encouraging and training caregivers to adopt active coping strategies has the potential to pave the way to relieve care burden by reducing caring fatigue and improving the care quality.ImpactAddressing stroke caregivers’ common fatigue highlights the importance of optimizing the recovery process to alleviate patients’ care dependency through better treatment and rehabilitation.